2023
DOI: 10.1097/mpg.0000000000003876
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Electrical Nerve Field Stimulation for Drug-Refractory Pediatric Cyclic Vomiting Syndrome

Katja Karrento,
Thangam Venkatesan,
Liyun Zhang
et al.

Abstract: Background: Cyclic vomiting syndrome (CVS) is a disabling condition frequently refractory to pharmacologic therapy. The aim of this study was to evaluate the effects of noninvasive, auricular percutaneous electrical nerve field stimulation (PENFS) as prophylactic therapy for pediatric CVS. Methods: Children 8–18 years with drug-refractory CVS were prospectively enrolled from a tertiary care CVS clinic. Subjects received 6 consecutive weeks of PENFS. CVS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…While the reliability of the long‐term follow‐up data beyond 6 months can be questioned, the results of the primary outcome and 3‐month follow‐ups included a fairly large cohort and is highly consistent with prior studies. These data replicate a prior randomized trial in pediatric DGBI, showing significant treatment effects compared to sham for 2–3 months and more recent, open‐label data 12,25,27,44 . The results may also be skewed, perhaps underestimated, since data was not systematically collected after the end of therapy at 4 weeks due to majority not returning to clinic after the 4th device placement.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…While the reliability of the long‐term follow‐up data beyond 6 months can be questioned, the results of the primary outcome and 3‐month follow‐ups included a fairly large cohort and is highly consistent with prior studies. These data replicate a prior randomized trial in pediatric DGBI, showing significant treatment effects compared to sham for 2–3 months and more recent, open‐label data 12,25,27,44 . The results may also be skewed, perhaps underestimated, since data was not systematically collected after the end of therapy at 4 weeks due to majority not returning to clinic after the 4th device placement.…”
Section: Discussionsupporting
confidence: 78%
“…Unfortunately, the significant number of patients lost to extended follow‐up makes it difficult to understand the long‐term sustainability of PENFS. The increase in API and NSS scores among females at the 6‐ and 12‐month mark likely indicates that repeat PENFS courses are necessary, supported by recent data on median response duration of 113 days in pediatric cyclic vomiting syndrome 27 . On the contrary, a prior PENFS study noted sustained benefits up to 12 months post treatment 20 .…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Despite the high prevalence of these disorders and the considerable negative impact on quality of life in children, no drug has ever received regulatory (FDA) approval for chronic abdominal pain in children or adolescents. Until now, no device had ever received clearance by the FDA, but several studies, including the one reported by Santucci et al have consistently demonstrated the efficacy of PENFS for DGBIs in children ( 1 7 ). Pediatric gastroenterologists, like many other pediatric subspecialists, still resort to using “off-label” medications to try to alleviate pain, in hopes of improving the lives of children and their families.…”
mentioning
confidence: 99%